A hybrid of 2D materials (MoS 2 and WS 2 ) as an effective performance enhancer for poly(lactic acid) fibrous mats in oil adsorption and oil/water separation - Tharnthip Krasian (2019)
© 2019 Elsevier B.V. Oil contamination in the environment has drawn increasing concern with regards the removal of oil spills. Herein, electrospun fibrous composite mats, based mainly on eco-friendly poly(lactic acid) (PLA), were fabricated with the ability to function as oil adsorbents and oil/water separators. The incorporation of two-dimensional materials, either molybdenum disulfide (MoS 2 ) or tungsten disulfide (WS 2 ) contributes to the enhancement in oil adsorption capacity of the neat PLA mats (7.75 g/g) by ∼89% and ∼102%, respectively. Using a grinding-assisted direct ultrasonication of the MoS 2 and WS 2 , the WS 2 -MoS 2 hybrid was facilely prepared in mild conditions with no requirement of a multi-step procedure. The presence of the hybrid at an optimal loading content in the PLA mats contributed to strengthening of the mats and, more importantly, a further increase of oil adsorption capacity to reach ∼190% enhancement in comparison with the neat PLA mats. The PLA/hybrid mats offer versatility in adsorbing various oils and providing good reusability with efficient adsorption performance of ∼90% during repeated use. The composite mats also behave as oil/water separators by functioning as oil adsorbents for floating oil on water surfaces and also acting as separation membranes in a simple gravity-driven filtration system. Effective separation of surfactant-stabilized oil/water emulsion is demonstrated with ∼70% flux recovery over separating cycles. The PLA/hybrid mats are promising candidates for the future treatment of oil contaminants in the natural environment.